PENGEMBANGAN BAHAN AJAR BERBANTUAN VIDEO YOUTUBE DALAM PEMBELAJARAN TEKS ANEKDOT - Dita Hasibuan; Dora Perawati Sihotang; Inez Christy Saragih; Monggun Maulidiya Siregar; Nova Muhairani Nasution; Yosi Aunike Sinuraya; Nurul Azizah; Trisnawati Hutagalung (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This studyaims to create YouTube video-based learning materials for teachinganecdotal texts to students at SMK Swasta 1 Parulian Medan. The approach usedis Research and Development (R&D) with the ADDIE development model, which includesthe stages of analysis, design, development, implementation, and evaluation. The results of the mini research show that traditional learning methods are not entirely effectivein improving student understanding. Learning materials designed through the integration ofYouTube videos have been proven to be effective in increasing student motivation and understanding ofanecdotal texts. Product evaluation shows the suitability of the media and its efficiency inimproving learning outcomes. The results of this study emphasize the importance of utilizingdigital media in teaching Indonesian language in vocational schools.